A method to estimate the longshore sediment transport at ebb‐tidal deltas based on their volumetric growth: application to the Guadiana (Spain–Portugal border) - Garel, Erwan; López‐Ruiz, Alejandro; Ferreira, Oscar (Earth Surface Processes and Landforms, 2019)
Current techniques assessing longshore sediment transport rates have large uncertainties, pleading for the development of alternative and complementary approaches. The present study proposes a method to estimate the decadal average rate of longshore transport at modern ebb-tidal deltas based on a sediment budget analysis of the outer shoal growth. This transport is obtained as the balance of the other contributions to the shoal with the total sediment input rate obtained from an inverse application of the inlet reservoir model. The method is applied to the Guadiana ebb-tidal delta, yielding an average longshore sediment transport rate (~85 000 m3 year(-1)) in good agreement with expectations for the region. It is exemplified that this decadal averaged rate can be used to improve longshore sediment transport expressions in order to study its variability over shorter time scales. At the Guadiana, the yearly longshore sediment transport from the improved formula ranges from ~25 000 m(3) (westward) to ~245 000 m(3) (eastward) and is related to the North Atlantic Oscillation index. Overall, the proposed method constitutes an alternative tool to constrain the average longshore sediment transport rate over decades in the vicinity of tidal inlets. It is applicable to ebb-tidal deltas where the outer shoal growth (from an early to a mature stage) is well documented by bathymetric maps, and where the main transport pathways towards the outer shoal can be specified. (c) 2019 John Wiley & Sons, Ltd. (c) 2019 John Wiley & Sons, Ltd. info:eu-repo/semantics/publishedVersion